Heart Rate Variability and Heart Rate Turbulence in HIV‐Infected Patients Receiving Combination Antiretroviral Therapy - Wongcharoen, Wanwarang (Ann Noninvasive Electrocardiol, 2013)
BACKGROUND: Previous studies have demonstrated the presence of autonomic dysfunction in human immunodeficiency virus (HIV)‐infected patients. However, the data in those receiving combination antiretroviral therapy (cART) are conflicting. The aim of this study was to assess the autonomic function using heart rate variability (HRV) and heart rate turbulence (HRT) analysis in HIV‐infected patients receiving cART. METHODS: Eighty‐one HIV‐infected patients receiving cART and 42 control subjects were enrolled in the study. The HRV and HRT parameters were assessed on 24‐hour digital Holter electrocardiogram recordings. RESULTS: Baseline characteristics were comparable between HIV‐infected and control subjects, except the higher fasting glucose and triglyceride and lower high‐density lipoprotein cholesterol observed in HIV‐infected patients. All components of HRV were significantly reduced in HIV‐infected patients. After adjustment with biochemical parameters, most of the HRV parameters were still significantly reduced in HIV‐infected patients. However, HRV parameters reflecting vagal activity were no longer different between 2 groups. In addition, HRT parameters did not differ between HIV‐infected and control subjects. The standard deviation of normal‐to‐normal intervals significantly correlated with CD4 lymphocyte counts in HIV‐infected patients but did not with protease inhibitors therapy. CONCLUSIONS: We demonstrated the overall decrease in HRV in HIV‐infected patients receiving cART. The metabolic disturbance observed in HIV‐infected patients possibly accounted for decreased vagal activity.